IMPLEMENTASI PEMBELAJARAN PAI PADA MASA PANDEMI COVID-19 DI SMP N 1 BUKIT SUNDI TAHUN AJARAN 2020/2021 - Roza Maifadillah (El-Rusyd, 2021)
During this pandemic, at SMP N 1 Bukit Sundi, students are required to be able to understand and master and apply the material provided by the teacher, one of which is PAI subjects. Therefore, in PAI subjects, inspirational teachers are needed who can improve students' abilities, with conditions where the learning system is not implemented face-to-face. This study aims to find out how to apply PAI learning during the covid-19 pandemic and, what are the obstacles encountered in implementing PAI learning during the Covid-19 pandemic class IX at SMP N 1 Bukit Sundi, Solok Regency. field (field research) with a qualitative approach. From the research that has been done, it can be concluded that the implementation of PAI learning during the covid-19 pandemic at SMP-N 1 Bukit Sundi there were 2 (1) PAI learning during this pandemic was carried out online using WhatsApp Group media and offline learning where students picked up and delivering the tasks given by the teacher once a week to school, (2) the perceived obstacles in learning during the pandemic, which the teacher feels include the lack of facilities and infrastructure to support PAI learning itself, which is felt by students, namely, not all student residences have quality good network, there are also some students who do not have Android phones, and parents of students, namely not all parents are able to provide explanations related to the material that students learn from their teachers, there are also some parents who are busy working so they cannot supervise their children in learning process.